Effect of Patient Body Mass Index, Recommendation for Weight Modification, and Nonmodifiable Factors on Patient Satisfaction. Issue 10 (15th May 2020) - Wells, Joel; Batty, Miles; Box, Hayden; Nakonezny, Paul A.
Abstract : Introduction: Patient satisfaction serves an increasingly important role in health care. Multiple nonmodifiable patient factors have been found to influence patient satisfaction. To the best of our knowledge, however, no study has investigated the influence of body mass index (BMI) on satisfaction scores. The objective of this study was to evaluate whether BMI and provider recommendation for patient weight modification were associated with patient satisfaction. Methods: We reviewed Press Ganey patient satisfaction survey scores from 3, 044 clinical encounters in an academic orthopaedic center between November 2010 and May 2017. Multiple patient factors, BMI, and recommendation for weight loss, or requirement of weight loss, before surgery were recorded. Patient satisfaction was operationalized as a binary outcome of completely satisfied or not completely satisfied, and multiple logistic regression was used to estimate the odds of being completely satisfied from the subset of potential predictors. Results: White patients (odds ratio [OR] = 1.340, 95% confidence interval [CI]: 1.113 to 1.584, P = 0.0007) and Medicare-insured patients (OR = 1.260, 95% CI: 1.044 to 1.521, P = 0.0164) were more likely to be completely satisfied, whereas patients being seen by a provider for the first time were less likely to be completely satisfied (OR = 0.728, 95% CI: 0.626 to 0.847, P < 0.0001). BMI, recommendation for weight loss, and requirement of weight modification before surgery were not found to be associated with patient satisfaction. Discussion: Neither patient BMI nor provider recommendation for weight loss, or as a requirement for surgery, was associated with patient satisfaction. Race, insurance status, and previous visits with the care provider were identified as nonmodifiable patient factors that influence patient satisfaction. Level of Evidence: Level III